2018
DOI: 10.1053/j.ajkd.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Acute Kidney Injury (AKI) Alerts With Automated Nephrologist Consultation on Detection and Severity of AKI: A Quality Improvement Study

Abstract: Implementation of the AKI alert system was associated with beneficial effects in terms of an improved rate of recovery from AKI. Therefore, widespread adoption of such systems could be considered in general hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 30 publications
7
91
1
Order By: Relevance
“…Recovery from AKI was defined as a return of serum creatinine to 1.2 times the baseline level. When the criterion of an increase in creatinine of 0.3 mg/dL was the only fulfilled criterion for AKI, the return of serum creatinine concentrations to a 0.2 mg/dL increase from baseline was used to define AKI recovery . In the cases of AKI requiring dialysis, the recovery of AKI was defined when dialysis was no longer needed and the creatinine value after stopping dialysis was less than 1.2 times the baseline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery from AKI was defined as a return of serum creatinine to 1.2 times the baseline level. When the criterion of an increase in creatinine of 0.3 mg/dL was the only fulfilled criterion for AKI, the return of serum creatinine concentrations to a 0.2 mg/dL increase from baseline was used to define AKI recovery . In the cases of AKI requiring dialysis, the recovery of AKI was defined when dialysis was no longer needed and the creatinine value after stopping dialysis was less than 1.2 times the baseline.…”
Section: Methodsmentioning
confidence: 99%
“…When the criterion of an increase in creatinine of 0.3 mg/dL was the only fulfilled criterion for AKI, the return of serum creatinine concentrations to a 0.2 mg/dL increase from baseline was used to define AKI recovery. 21,22 In the cases of AKI requiring dialysis, the recovery of AKI was defined when dialysis was no longer needed and the creatinine value after stopping dialysis was less than 1.2 times the baseline. Recovery from 0 to 30 days after AKI was analysed and events with missing serum creatinine follow-up measurements were censored at the last day of the test.…”
Section: Outcome Variablementioning
confidence: 99%
“…Automatic electronic alert, based on the laboratory test results and with a prompt on nephrology consultation, would be a promising way to move forward. A recent study from Korea showed that after implementation of an electronic alert system, the frequency of stage 2 or 3 AKI decreased from 32% to 27%, and recovery of kidney function within 30 days increased from 56% to 80% when compared with historic control . Early nephrology consultation was probably the reason of a better outcome as it was associated with lower rates of failure to follow‐up kidney function, and higher rates of recovery of kidney function …”
Section: Epidemiology Of Aki In Hong Kongmentioning
confidence: 99%
“…12 Early nephrology consultation was probably the reason of a better outcome as it was associated with lower rates of failure to follow-up kidney function, and higher rates of recovery of kidney function. 12…”
Section: Practical Problemsmentioning
confidence: 99%
“…With advances in the electronic medical record systems, there are options for e-alerts pertaining to CA-AKI [4]. In the hospital setting, e-alerts have been associated with a lower risk of overlooked HA-AKI, severe HA-AKI, improved odds of nephrologist referral, and improved HA-AKI recovery [27]. Similarly, a 3-month descriptive observational study demonstrated the ability to use CA-AKI alerts at the hospital, whether or not patients were actually admitted to the hospital [28].…”
Section: Discussionmentioning
confidence: 99%